2005
DOI: 10.1111/j.1523-1755.2005.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary calcium is a determinant of bone mineral density in elderly men participating in the InCHIANTI study

Abstract: High calcium excretion is associated with a decreased trabecular BMD in elderly men and may predispose men to trabecular bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 38 publications
2
40
0
3
Order By: Relevance
“…Our results contrast with those of prior smaller-sized studies. In the InChianti Study (n=595) (10), an association between serum calcium and 24-hour urinary calcium excretion was observed in men but not women. Peacock et al (20) found a positive association between serum calcium load and urinary calcium excretion in 72 men and women.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our results contrast with those of prior smaller-sized studies. In the InChianti Study (n=595) (10), an association between serum calcium and 24-hour urinary calcium excretion was observed in men but not women. Peacock et al (20) found a positive association between serum calcium load and urinary calcium excretion in 72 men and women.…”
Section: Discussionmentioning
confidence: 95%
“…Hypercalciuria was extensively studied in relation to kidney stone formation (8) and osteoporosis (9,10). However, population-based data on urinary calcium excretion are scarce, and the relationship between serum calcium and urinary calcium excretion or between circulating 25(OH)D levels and urinary calcium excretion has surprisingly not been fully explored or remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It has been mainly studied in patients producing kidney stones but was also found in 20% of osteoporotic women and 10% of the general population (2)(3)(4). Patients with idiopathic hypercalciuria are characterized by high intestinal absorption and low tubular reabsorption of calcium and may have decreased bone mass (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Defects of calcium reabsorption in both proximal and distal tubules were observed in hypercalciuric patients with or without stones (9,10). Decreased bone mineral density (BMD) may result from the negative balance between urine loss and enteral absorption of calcium (3,4). However, low BMD was associated with high calcium absorption and could be supported by a primary defect of calcium handling in intestinal, bony, and kidney tubular cells (7,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation